2020
DOI: 10.1007/s42452-020-2252-z
|View full text |Cite
|
Sign up to set email alerts
|

Porous chitosan by crosslinking with tricarboxylic acid and tuneable release

Abstract: Chitosan hydrogels crosslinked with 1,3,5-benzene tricarboxylic acid (BTC) are readily prepared at room temperature by adding aqueous chitosan solution dropwise into BTC-ethanol solution. Highly interconnected porous chitosan materials are subsequently prepared by freeze-drying the chitosan hydrogels. These chitosan materials show porous structures with smaller pores than conventionally prepared chitosan hydrogels via crosslinking with NaOH, genipin or sodium triphosphate. This method of forming chitosan hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…The morphological characteristics of the KT-CTS gel showed that it has a compact and dense structure. This was also observed by Yanget al [29]. Nevertheless, other researchers observed la-…”
Section: Discussionsupporting
confidence: 76%
“…The morphological characteristics of the KT-CTS gel showed that it has a compact and dense structure. This was also observed by Yanget al [29]. Nevertheless, other researchers observed la-…”
Section: Discussionsupporting
confidence: 76%
“…LS is quickly released from the NPs in the initial 10 h [ 125 ] Ionic gelation method CS porous NPs Oil Red O and Rhodamine B. Denser hydrogels and Highly interconnected macropores, around 50–200 nm and relatively uniformly around 50–100 nm, SF methods A fast release for 1 h, then reaching the equilibrium concentration [ 126 ] Ionic interaction with dextran sulfate (DS) as a crosslinker CS NPs Double-stranded siRNA Irregular morphology, d = 353–1083 nm. SS methods DS and CS concentration influenced the size of NPs.…”
Section: Drug Release From Csnpsmentioning
confidence: 99%
“…The swelling of CSNPs, at a higher pH value (7.4) may increase, which would allow release media to penetrate deeper into the polymer matrix, converting the glassy polymer to a rubbery state [ 134 ]. Drug molecules were able to diffuse out of the CSNPs more quickly and release quickly [ 126 ].…”
Section: Drug Release From Csnpsmentioning
confidence: 99%
“…A physical process occurs when experimental parameters such as pH or temperature are varied, or through the addition of counterions, while a chemical process takes place through the addition of chemical crosslinkers such as glutaraldehyde or diisocyanate [70]. The addition of such chemical agents modifies the chemical properties of pure chitosan-based hydrogels but can give rise to some toxicological concerns; in this regard, the use of biocompatible agents such as genipin may be a suitable approach [136,137].…”
Section: Chitosan-based Hydrogelsmentioning
confidence: 99%